3D-finite element pavement structural model for using with traffic speed deflectometers. Issue 12 (15th October 2022) - Mabrouk, Gamal M.; Elbagalati, Omar S.; Dessouky, Samer; Fuentes, Luis; Walubita, Lubinda F.
ABSTRACT : The traditional practice for pavement structural capacity evaluation is mostly dependent on the falling weight deflectometer (FWD) measurements. However, this practice has several challenges due to its stationary nature. Recently, a Rolling Weight Deflectometer (RWD), capable of measuring the pavement deflections at regular traffic speeds, has been introduced into the market. This research aims to develop a finite element (FE) model simulating pavement structural response under the moving RWD loads. This model could be further utilised for accurately estimating pavement layers mechanical characteristics. The model was successfully validated utilising the RAPTOR (a commercially available RWD) data collected on the National Center for Asphalt Technology (NCAT) test track. A good correlation between the simulated and the measured values was found – yielding an average root mean square percentage error (RMSPE) of approximately 2.40% between the RAPTOR and the FE deflections.